The use of automated writing evaluation (AWE) in developing language proficiency: a study from the learners’ perspective - Abd Razak, Harniza; Lotfie, Maskanah Mohammad; Md Zamin, Ainul Azmin (2020)
The focus of this research is on the perceptions of English as a second language (ESL) learners on the use of Automated Writing Evaluation (AWE) in improving their written English. By employing quasi-experimental research design, the effectiveness of the computer-generated feedback, which is known as WriteLab in improving ESL learners’ writing is investigated. It is an online writing tool which brings in the latest developments of natural language processing and machine learning. The present preliminary study which is part of a bigger research indicated that there is a positive perception as viewed by the students. The statistical analysis also demonstrated that there is a positive correlation between the students’ perception and the quality of the essays that they produced. Recommendations for further research and implications for instructors are also discussed.